Perancangan Sistem Informasi Pengaduan Masyarakat Berbasis Web Dengan Menggunakan Framework Laravel - Avandy Wijaya; Indah Fenriana; Lianny Wydiastuty Kusuma; Ellysha Kusuma (ALGOR, 2022)
In this day and age technology is growing rapidly and technology has an important role in all aspects of human life, especially websites which are currently becoming media information that is very easy to achieve using only the internet. Website is a web page that can be accessed by the public using the internet, and the website also has a domain name that is owned by each website. In addition, the website can also be opened via computers, laptops, smartphones, tablets, and so on. The purpose of this research is to design a system that has the Create and Read feature which will later be used by the public in reporting, to design a website public complaint system so that information sent by the public to the government is fast and accurate, based on a website-based public complaint system located on the website. In it there is a feature that can send an email to notify that the information provided by the public has been received, or it is resolved with the SMTP feature which later on the public can find out the complaint process. The system made is web-based using the Laravel framework, the system is made based on the public complaint system, consisting of people who can upload and send complaints to the government as well as people who see the status of their complaints, besides that there are admins who can view and process complaints, can add officers, and can print report data in the form of pdf. Officers can only view and process complaints and can print report data in the form of pdf, where users of this system are admins and officers from government and the community are users.